Tailored crystalline width and wall thickness of an annealed 3D carbon foam composites and their mechanical properties. (February 2019) - Marx, J.; Roth, S.; Brouschkin, A.; Smazna, D.; Mishra, Y.K.; Schulte, K.; Adelung, R.; Fiedler, B.
Abstract: Carbon nanostructures in form of 3D carbon foams are mainly popular in materials community because of their ultralow densities, variable morphologies, and remarkable properties, etc. One of these foams is Aerographite, which exhibits a tetrapodal interconnected morphology. Similar to other synthetic carbon structures, the lattice defects are formed during the synthesis of Aerographite, which can be healed by a post-thermal treatment. Aerographite shows a property dependency on wall thickness (number of graphitic layers), which affects both, the electrical and mechanical properties. In this study, the wall thickness is tailored by varying of the total reaction time during the replication process. The influence of the thermal treatment of Aerographite on its mechanical performance in an Aerographite-epoxy nanocomposite, by determining the fracture toughness (K1C ) in three-point bending tests (SEN-3PB), is investigated. An increase of the fracture toughness with increasing wall thickness is observed for untreated Aerographite. The graphitization of Aerographite leads to a reduction of the mechanical properties, by increasing the crystalline width. Consequently, the measured fracture toughness is dependent on the graphitization, the calculated crystalline width and the wall thickness of tubes in the hollow Aerographite tetrapodal network. Finally, based on these relations, a phenomenological mechanical failure model is developed and briefly discussed. Graphical abstract: Image 1